HbaR, a 4-Hydroxybenzoate Sensor and FNR-CRP Superfamily Member, Regulates Anaerobic 4-Hydroxybenzoate Degradation by Rhodopseudomonas palustris - Egland, Paul G. (American Society for Microbiology, 2000)
Under anaerobic conditions, structurally diverse aromatic compounds are catabolized by bacteria to form benzoyl-coenzyme A (benzoyl-CoA), the starting compound for a central reductive pathway for aromatic ring degradation. The structural genes required for the conversion of 4-hydroxybenzoate (4-HBA) to benzoyl-CoA by Rhodopseudomonas palustris have been identified. Here we describe a regulatory gene, hbaR, that is part of the 4-HBA degradation gene cluster. An hbaR mutant that was constructed was unable to grow anaerobically on 4-HBA. However, the mutant retained the ability to grow aerobically on 4-HBA by an oxygen-requiring pathway distinct from the anaerobic route of 4-HBA degradation. The effect of the HbaR protein on expression of hbaA encoding 4-HBA-CoA ligase, the first enzyme for 4-HBA degradation, was investigated by using hbaA::′lacZ transcriptional fusions. HbaR was required for a 20-fold induction of β-galactosidase activity that was observed with a chromosomal hbaA::′lacZ fusion when cells grown anaerobically on succinate were switched to anaerobic growth on succinate and 4-HBA. HbaR also activated expression from a plasmid-borne hbaA-′lacZ fusion when it was expressed in aerobically grown Pseudomonas aeruginosa cells, indicating that the activity of this regulator is not sensitive to oxygen. The deduced amino acid sequence of HbaR indicates that it is a member of the FNR-CRP superfamily of regulatory proteins. It is most closely related to transcriptional activators that are involved in regulating nitrate reduction. Previously, it has been shown that R. palustris has an FNR homologue, called AadR, that is also required for 4-HBA degradation. Our evidence indicates that AadR activates expression of hbaR in response to anaerobiosis and that HbaR, in turn, activates expression of 4-HBA degradation in response to 4-HBA as an effector molecule.